MANAJEMEN KRISIS PUBLIC RELATIONS KOMUNITAS AMAZING TRUEHEALTH DALAM MENGHADAPI ISU HOAKS KANGEN WATER - Hadiniyati, Ghina; Abdurrahman, Muhammad Sufyan (PRoListik : Jurnal Ilmu Komunikasi, 2022)
Along with the development of media, society is getting easier to produce or access news. It certainly gives a positive impact, but on the other hand also causes a negative impact one of them is the rampant circulation of news hoaks or the truth of the news cannot be accounted for. One of the hoaks news that circulated widely in the media is Kangen Water hoaks issue in November 2017. The issue developed into a crisis for the Amazing Community True Health (KAT) as Kangen Water’s first and largest distributor community in Indonesia. This research use qualitative method and study case technique. Along the collecting data process, researcher use deep interview method to a few respondents. There are presedent and PR of KAT as ket informants, Kangen Water distributor as supporting informant, and PR practitioner as expert informant. Based on the results of the analysis of the researcher, in implementing the crisis prevention efforts, KAT implements several strategies, one of them is to submit an apology, admit the mistake, explain the problem, and change the views and perceptions related to Kangen Water benefits widely. Researcher can also conclude that the management of crisis of public relations conducted by KAT has reached its goals marked by the return of distributor’s confidence to do the business after crisis, positive responses from Kemenkes to the efforts made by KAT in handling this crisis, and positive responses from public in social media.